2014
DOI: 10.1093/aje/kwu029
|View full text |Cite
|
Sign up to set email alerts
|

Age, Period, and Cohort Effects in Psychological Distress in the United States and Canada

Abstract: Although treatment utilization for depression and anxiety symptoms has increased substantially in the United States and elsewhere, it remains unclear whether the underlying population distribution of psychological distress is changing over time. We estimated age, period, and cohort effects using data from 2 countries over more than 20 years, including National Health Interview Surveys from 1997 to 2010 (n = 447,058) and Canadian Community Health Surveys from 2000 to 2007 (n = 125,306). Psychological distress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 35 publications
5
69
2
3
Order By: Relevance
“…Girls with and without intellectual disabilities report higher incidence rates of potential mental health problems than boys at both waves, with incidence rates increasing for girls from Wave 2 to Wave 4. Overall, these findings are consistent with general research showing distress peaking at late adolescence (Keyes et al., ) and with adolescents with intellectual disabilities experiencing more persistent mental health problems from a younger age than adolescents without intellectual disabilities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Girls with and without intellectual disabilities report higher incidence rates of potential mental health problems than boys at both waves, with incidence rates increasing for girls from Wave 2 to Wave 4. Overall, these findings are consistent with general research showing distress peaking at late adolescence (Keyes et al., ) and with adolescents with intellectual disabilities experiencing more persistent mental health problems from a younger age than adolescents without intellectual disabilities.…”
Section: Discussionsupporting
confidence: 90%
“…Extensive epidemiological research concerning adolescents in the general population in a number of countries (see Collishaw, ; for a recent review) has reported high and increasing rates of depression, anxiety, emotional disorders, self‐harm and suicide, and in some countries conduct problems/antisocial behaviour among adolescents, with rates of distress peaking in late adolescence (Keyes et al., ). Socio‐economic factors and adversities such as maternal depression and bullying/peer victimization are consistently associated with adolescent mental health problems; while levels of peer bullying have been largely stable or decreasing, levels of maternal depression have been increasing (Schepman et al., ) and disparities in rates of adolescent emotional problems between high‐income and low‐income families have widened sharply (Gore Langton, Collishaw, Goodman, Pickles, & Maughan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on major depression among older persons conducted during the same period report stable prevalence . In contrast, time trend studies focusing mainly on younger and middle‐aged populations generally report higher prevalence of depression and depressive symptoms among later born cohorts , but the prevalence is also reported to be stable over time .…”
Section: Discussionmentioning
confidence: 95%
“…An increase in depression is suggested for younger and middle‐aged populations. Among older adults, the prevalence of major depression has been found to be stable , while milder forms of depression have been reported to increase , decrease , or fluctuate over time. Studies also show inconclusive time trend results .…”
Section: Introductionmentioning
confidence: 99%
“…17 A period effect in sleep duration would imply that factors which are common across adolescents in all age groups (eg, increasing screen time with mobile technology) may be fruitful factors to explore as potential mechanisms and targets for intervention. A cohort effect in sleep duration would imply that factors which are becoming increasingly common for recent cohorts as children enter into adolescence (eg, increased psychological distress, 18 increased nonmedical use of prescription medication 19 ) underlie trends over time, and that efforts to improve sleep should focus on these increasing factors before adolescence begins.…”
mentioning
confidence: 99%